Comparison of Active Range of Motion and Force Grip - Papakosta Ξανθίππη; Sikaras Ευάγγελος; Kitsios Αθανάσιος; Hatzimanouil Δημήτριος (Inquiries in Physical Education and Sport, 2014)
The purpose of the present research was to assess the influence of the visual problem on joint’s range of motion (ROM) (hip–knee-elbow–wrist) and on hand grip strength in blind children of 7-13 years old. In the research took place 30 children, 10 of which were blind and 20 had normal vision. The measurements were obtained using a Myrin and Brodin goniometer for ROM and Jamar hydraulic hand dynamometer for hand grip strength. For statistical analysis it was used nonparametric Mann-Whitney test (p<.05). Significant deference was observed in the range of motion of all joints except elbow flexion where there was no statistical significant difference (children with normal vision were obtaining higher numbers). There was no statistical significant difference in hand grip strength between blind and sighted children (children with normal vision were obtaining higher numbers). Conclusively, interfering programs from young age are very important to diminish those differences in active range of motion (AROM) and hand grip strength.